2007
DOI: 10.1073/pnas.0701669104
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Spem1 causes aberrant cytoplasm removal, sperm deformation, and male infertility

Abstract: We identified a previously uncharacterized gene, spermatid maturation 1 (Spem1), encoding a protein exclusively expressed in the cytoplasm of steps 14 -16 elongated spermatids in the mouse testis. This protein contains no known functional domains and is highly conserved across mammalian species. Male mice deficient in Spem1 were completely infertile because of deformed sperm characterized by a bent head wrapped around by the neck and the middle piece of the tail. We show that lack of Spem1 causes failure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 50 publications
7
147
1
1
Order By: Relevance
“…Akin to Ube2j1 Ϫ/Ϫ mice, SPEM1 Ϫ/Ϫ males (but not females) are sterile and their sperm are ϳ85% immotile because of severe deformations in the head/neck region, caused by retention of cytoplasmic remnants. The ultrastructural characteristics are strikingly similar to our observations in Ube2j1 Ϫ/Ϫ sperm (38). SPEM1 interacts with UBQLN1 (ubiquilin 1) at the manchette of elongating spermatids (39).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Akin to Ube2j1 Ϫ/Ϫ mice, SPEM1 Ϫ/Ϫ males (but not females) are sterile and their sperm are ϳ85% immotile because of severe deformations in the head/neck region, caused by retention of cytoplasmic remnants. The ultrastructural characteristics are strikingly similar to our observations in Ube2j1 Ϫ/Ϫ sperm (38). SPEM1 interacts with UBQLN1 (ubiquilin 1) at the manchette of elongating spermatids (39).…”
Section: Discussionsupporting
confidence: 74%
“…An intriguing case is SPEM1 (spermatid maturation 1), a protein of unknown molecular function, which is expressed exclusively in elongating spermatids between steps 14 and 16, implying a function in cytoplasm removal and/or spermiation (38). Akin to Ube2j1 Ϫ/Ϫ mice, SPEM1 Ϫ/Ϫ males (but not females) are sterile and their sperm are ϳ85% immotile because of severe deformations in the head/neck region, caused by retention of cytoplasmic remnants.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed a slightly increased level of phosphorylated p70S6 kinase ( Figure 4A), suggesting enhanced protein synthesis in TNAP-Atg7 −/− mouse testes. Similar to Spem1-knockout mice [16], we found that the polyubiquitinated protein level increased by 1.5-fold in Atg7-deficient testes compared with Atg7 Flox/ Flox ones ( Figure 4B and 4C), indicating the inhibition of protein degradation. Consistent with findings from Atg7 knockout in other tissues [9,17,18], LC3-I but not the membrane-associated form LC3-II was accumulated in Atg7-deficient testes ( Figure 4D).…”
Section: Autophagic Flux Is Disrupted In the Testis Of Tnap-atg7 −/− supporting
confidence: 57%
“…A floxed Miwi2 allele (Miwi2 lox ) was generated by conventional ES cell targeting through homologous recombination. 51 A conditional Miwi2-targeting vector was constructed using Quick & Easy Red/ET Conditional Knock Out Kit-loxP kit (GeneBridge, Cat#: K005) according to the manufacturer's protocol. Briefly, two loxp site-containing PGK donor cassettes (loxP-pgk-Neo r -loxP) were inserted into introns 8 and 12 of Miwi2 gene contained in a BAC clone (BAC#:RP23-340G24, Children's Hospital Oakland Research Institute, Oakland, CA, USA), and the first PGK cassette was deleted by a Cre-expressing vector fragment (706-Cre) to retain a 34-bp loxp site sequence in the targeting vector (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%